'For environment read conservation': New Zealand as an example of green purity. (4th August 2014) - Wells, Philippa
The international official and commercial face often presented by New Zealand is one of environmental consciousness. Legal and administrative structures reinforce a message of environmental responsibility. However, evidence does not paint such a rosy picture, suggesting that a structural emphasis on conservation/preservation fails to address problems of wider environmental importance. With fresh water as context, and a case study as example, this paper locates conservation/preservation in the New Zealand environmental landscape. In addition, it offers a brief critique of alternatives to the management of this most vital of resources and notes some wider environmental implications.